2003
DOI: 10.1200/jco.2003.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of the Efficacy and Tolerability of Two Dosing Regimens of the Farnesyl Transferase Inhibitor, R115777, in Advanced Breast Cancer

Abstract: The farnesyl transferase inhibitor R115777 has demonstrated clinical activity in patients with metastatic breast cancer, and the ID regimen has a significantly improved therapeutic index compared with the CD regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(125 citation statements)
references
References 19 publications
4
119
1
1
Order By: Relevance
“…Tumor regression in this mouse model was associated with a reduction in MAP kinase activity and an increase in apoptosis (Norgaard et al 1999). However, Johnston et al (2003) did not find a correlation between response to the FTI, R 155777, and expression of HER-2/ neu, in patients with metastatic breast cancer.…”
Section: Effects Of Ftis Independent Of Rasmentioning
confidence: 87%
See 3 more Smart Citations
“…Tumor regression in this mouse model was associated with a reduction in MAP kinase activity and an increase in apoptosis (Norgaard et al 1999). However, Johnston et al (2003) did not find a correlation between response to the FTI, R 155777, and expression of HER-2/ neu, in patients with metastatic breast cancer.…”
Section: Effects Of Ftis Independent Of Rasmentioning
confidence: 87%
“…However, as described later, despite the initial belief that FTIs act solely through the Ras pathway, it is now apparent that they have other effects on several cellular signal transduction processes, which may be independent of Ras (Johnston & Kelland 2001). This hypothesis may explain why FTIs have activity in breast cancer models preclinically (Kelland et al 2001), and may be active clinically (Johnston et al 2003), despite the fact that breast cancers rarely have mutations of ras (Clark & Der 1995a). …”
Section: Targeted Therapies In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Lonafarnib is synergistic with cisplatin and additive with gemcitabine in vitro, and active against breast carcinoma xenografts [31,32,42]. FTIs alone are clinically very active in breast cancer [21]: a phase II study of tipifarnib dosed continuously in 76 advanced breast cancer patients demonstrated 4 PR and 6 SD lasting >24 weeks, and when dosed for 21 out of 28 days, 5 PRs and 3 prolonged SD were noted in 35 patients [21,24]. Therefore, further exploration of lonafarnib and other FTIs with chemotherapy in breast cancer may be warranted.…”
Section: Discussionmentioning
confidence: 99%